Harvesting rainwater from buildings - Haq, Syed Azizul (Springer, 2017)
The present book describes in detail all aspects of rainwater harvesting, including the basic concepts, procedures, opportunities and practice of rainwater harvesting mainly focusing its application in buildings of various occupancies and sizes. It provides a user-friendly methodology for the planning, design, construction and maintenance of rainwater harvesting infrastructure, in buildings and its premise, as a supplement to conventional water supplies. It highlights the application of plumbing technology, which is an important aspect of rainwater harvesting in buildings. It also includes global rainfall scenario and brief notes on all the elements of rainwater harvesting used in buildings. It is a valuable reference resource for policy and decision-makers, as well as for engineers, architects and students.
Keywords: Rainwater.; Water harvesting.; Civil engineering.; Environmental engineering.; elektronické knihy; electronic books